Robust Low Friction Antibiotic Coating of Urethral Catheters Using a Catechol-Functionalized Polymeric Hydrogel Film - Yang, Kisuk; Kim, Kyuri; Lee, Eunjee A.; Liu, Sophie S.; Kabli, Sara; Alsudir, Samar A.; Albrahim, Shahad; Zhou, Angela; Park, Tae Gwan; Lee, Haeshin; Almalik, Abdulaziz M.; Karp, Jeffrey M.; et al. (Frontiers in Materials, 2019)
Indwelling urethral catheters are widely used in hospitalized patients however they are associated with bacterial infection and biofilm formation due to the suboptimal surface properties of the elastic materials used for the catheters. Although there are several antibacterial coating technologies to modify the surface properties of the catheter including hydrophilic polymeric coating, the risk of infection is still high given the absence of reactive functional groups on the surface of elastomers. In this study, we describe the use of catechol-functionalized hydrophilic polymers and explore strategies to create antibacterial hydrogel coatings. Three different types of catechol-functionalized polymers, chitosan, hyaluronic acid, and human serum albumin were synthesized and deposited using simple dip-coating method. All of the tested polymers could coat different types of elastomers widely used for urethral catheters independent to the surface properties, and the thickness of the coating could be controlled by the number of depositions. The coating formed stable water-containing lubricant surface beneficial as a physical repellant of microbial attachment. In addition, the coating could be combined with additional antibacterial agents such as silver nanoparticles to maximize the antibacterial effect on the surface of urethral catheter materials.